2010
DOI: 10.1016/s1607-551x(10)70044-9
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol Versus Low Dose Tramadol‐paracetamol for Patient Controlled Analgesia During Spinal Vertebral Surgery

Abstract: Pain intensity may be high in the postoperative period after spinal vertebral surgery. The aim of the study was to compare the effectiveness and cost of patient controlled analgesia (PCA) with tramadol versus low dose tramadol-paracetamol on postoperative pain. A total of 60 patients were randomly divided into two groups. One group received 1.5 mg/kg tramadol (Group T) while the other group received 0.75 mg/kg tramadol plus 1 g of paracetamol (Group P) intravenously via a PCA device immediately after surgery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…21 Similarly, tramadol/acetaminophen combination was reported to show superior pain control over acetaminophen alone after vertebral surgery. 25 …”
Section: Discussionmentioning
confidence: 99%
“…21 Similarly, tramadol/acetaminophen combination was reported to show superior pain control over acetaminophen alone after vertebral surgery. 25 …”
Section: Discussionmentioning
confidence: 99%
“…They concluded that paracetamol reduce the severity of postoperative pain (25). In another study, Emir et al compared the analgesic effect of tramadol plus paracetamol and tramadol alone on the spinal surgery and reported a higher e cacy of paracetamol (26). Mo di et al also conducted a study on 80 patients with renal pain and found that intravenous paracetamol to be a safe and effective drug with no remarkable side effects in relieving pain in renal patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another study which is in agreement with our results comes from Emir et al . [11] who compared the effectiveness of tramadol versus low dose tramadol and paracetamol on postoperative pain using numeric rating pain scale in spine vertebral surgery and found that pain scores were significantly lower in the group that received low dose tramadol and paracetamol combination than that in the group that received tramadol alone. Kiliçaslan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Emir et al . [11] found that additional analgesic requirement and the total dose of tramadol were lower in Group P (tramadol-paracetamol) than in Group T (tramadol). Kiliçaslan et al .…”
Section: Discussionmentioning
confidence: 99%